Autoantibody clusters in childhood-onset systemic lupus erythematosus: Insights from a multicenter study with 912 patients - Trindade, Vitor C; Bonfá, Eloisa; Sakamoto, Ana P; Terreri, Maria T; Aikawa, Nádia E; Fiorot, Fernanda J; Pitta, Ana C; Balbi, Verena A; N Rabelo, Carlos; Silva, Marco F; Islabão, Aline G; Novak, Glaucia V; et al. (My University, 2025)
Objective: To identify clusters of autoantibodies in a large cSLE population and to verify possible associations between different autoantibody clusters and the following variables: demographic data, cumulative clinical and laboratory manifestations, disease activity, cumulative damage and mortality. Methods: A cross-sectional study was performed in 27 Pediatric Rheumatology University centers, including 912 cSLE patients. The frequencies of seven selected autoantibodies (anti-dsDNA, anti-Ro/SSA, anti-La/SSB, anti-Sm, anti-RNP, aCL IgM and/or IgG and LA) were used for cluster analysis using the K-means method. Results: Four distinctive antibody clusters were identified. Cluster 1 (n = 322; 35.31%) was characterized by anti-dsDNA (61.18%), low frequency of antiphospholipid antibodies (<10%), and lower frequency of cutaneous, articular manifestation (p < 0.05) and hypocomplementemia (p < 0.001) compared to the other groups. Cluster 2 (n = 158; 17.32%) comprised anti-dsDNA (93.04%), aCL (87.34%) and LA (39.87%) and higher frequencies of thrombocytopenia (p = 0.006) and antiphospholipid syndrome (p < 0.001) than the other clusters. Cluster 3 (n = 177; 19.41%) was characterized by anti-dsDNA (81.36%), anti-Sm (100%) and anti-RNP (44.63%) antibodies, as well as a higher frequency of proteinuria compared to cluster 4 (58.15% vs 56.13% vs 64.00% vs 49.80%, p = 0.031). Cluster 4 (n = 255; 27.96%) consisted of all 7 autoantibodies, with predominance of anti-dsDNA (72.55%), anti-Ro/SSA (89.8%) and anti-La/SSB (45.88%), with no specific clinical pattern, except by higher pulmonary damage (p = 0.017). Conclusions:Our study suggests that, within the context of cSLE, the coexistence of anti-dsDNA with antiphospholipid autoantibodies is linked to an elevated incidence of antiphospholipid syndrome. This association does not coincide with a proportionate increase in the occurrence of nephritis. Conversely, the cluster of anti-dsDNA with anti-Ro/SSA and anti-La/SSB antibodies was associated with pulmonary damage, requiring close surveillance.
Keywords: antiphospholipid syndrome; autoantibody; Childhood-onset systemic lupus erythematosus; cluster analysis; pulmonary damage